Review: Advances in Self-Preservation Techniques in Cosmetics Using Hurdle Technology - Senthilkumar, K.; Vijayalakshmi, A. (South Eastern European Journal of Public Health, 2024)
Preservatives are essential in cosmetic products to prevent microbial growth, extending product shelf life and ensuring user safety by minimizing infection risks. While traditional chemical preservatives have long been effective in protecting against microbial contamination, growing consumer concerns over their safety and potential health impacts are prompting a shift toward preservative-free or self-preserving cosmetic formulations. This shift has increased interest in developing products that maintain antimicrobial effectiveness without synthetic preservatives, with hurdle technology emerging as a promising approach. Originally applied in the food industry in the 1970s, hurdle technology involves combining multiple preservation strategies to inhibit microbial growth without relying on traditional preservatives. In cosmetic applications, hurdle technology can reduce or eliminate the need for synthetic preservatives by implementing several protective measures. These “hurdles” may include high manufacturing standards, protective packaging, emulsions that limit microbial growth, controlled water activity, and pH adjustments to create an environment less conducive to microbial survival. This review explores the adaptation of hurdle technology principles in cosmetics, focusing on techniques for creating self-preserving formulations. It highlights the role of multifunctional ingredients with natural antimicrobial properties, such as plant-derived essential oils, which can serve as alternatives to chemical preservatives. These ingredients not only inhibit microbial growth but also provide additional benefits, aligning with consumers' growing preference for natural, safe, and effective skincare options.